Strategic Analysis PT. Panorama Sentrawisata, TBK. (PANR) - Putu Devangga Makarabaja (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study discusses the strategic analysis of PT. Panorama Sentrawisata Tbk. (PANR), a tourism company operating in Indonesia and listed on the Indonesian Stock Exchange. In the context of industrial recovery after the COVID-19 pandemic, PT. Panorama is faced with the challenge of designing a sustainable and competitive strategy. Based on various analyses, including the EFE, IFE, BCG, and QSPM matrices, this research recommends a product development strategy to develop new tourism services and expand into the concert promoter business. This step was taken as an effort to attract tourist interest and increase the company's competitiveness. This research emphasizes the importance of detailed planning and youth workforce development to understand current market trends.